VivoFollow 2: Distortion-Free Multiphoton Intravital Imaging - Vladymyrov, Mykhailo; Haghayegh Jahromi, Neda; Kaba, Elisa; Engelhardt, Britta; Ariga, Akitaka (Frontiers in Physics, 2020)
Intravital multiphoton microscopy has become one of the central tools in the investigation of dynamic cellular activity and function in living animals under nearly physiological conditions and is particularly important for studying the dynamic immune system. During intravital imaging in mice, periodic motion of tissue caused by respiration induces significant shifts of the imaged region. In slow laser scanning imaging modalities such as multiphoton microscopy this movement can lead to considerable distortion and discontinuity in 3D of the acquired images. Here, we introduce VivoFollow 2, a toolkit that concurrent with image acquisition performs a precise measurement of the respective image distortion enabling subsequent automated correction of the imaging data. Recovery of one 3D image stack, corresponding to the tomographic tissue sectioning by the optical plane from each single raw image stack, preserves the time continuity within each image stack. Implementation of VivoFollow 2 thus enables a minimization of motion artifacts in tissues exposed to periodic movements and allows for long term time-lapse imaging and subsequent precise image analysis of the dynamics of cellular and humoral factors in vivo.